Comprehensive expression analysis reveals several miRNAs against acute pancreatitis via modulating autophagy: miRNAs against acute pancreatitis - Su, Xiaoju; Kong, Fanyang; Zhang, Qichen; Jiang, Mengni; Wang, Lei; Kong, Xiangyu; Du, Yiqi (Cellular and Molecular Biology, 2023)
Acute pancreatitis (AP) had been one of the main reasons for hospitalization worldwide. However, the mechanisms related to AP remained to be unclear. This study identified 37 miRNAs and 189 mRNAs were differentially expressed in pancreatitis and normal samples. Bioinformatics analysis showed DEGs were significantly related to PI3K-Akt signaling, FoxO signaling, Oocyte meiosis, Focal adhesion, and Protein digestion and absorption. By constructing a signaling-DEGs regulation network, we found COL12A1, DPP4, COL5A1, COL5A2, and SLC1A5 were related to regulating Protein digestion and absorption, THBS2, BCL2, NGPT1, EREG, COL1A1 were related to regulating PI3K signaling, CCNB1, CDKN2B, IRS2, PLK2 were related to modulating FOXO signaling. Next, we constructed 1 miRNA-mRNA regulation network in AP, consisting of 34 miRNAs and 96 mRNAs. The protein-protein interaction networks and the miRNA-targets networks analysis show that hsa−miR−199a−5p, hsa−miR−150, hsa−miR−194, COL6A3 and CNN1 acted as hub regulators in AOf note, through comprehensive expression analysis, we found several miRNAs and mRNAs were significantly related to modulating autophagy signaling in AP, including hsa−miR−181c, hsa−miR−181d, hsa−miR−181b, hsa−miR−379 and hsa−miR−199a−5Overall, this study screening differently expressed miRNAs in AP and revealed miRNA- autophagy regulation may serve as a potential prognosis and Therapeutic marker for AP.